Participation of NMDA and kainate receptors of paraventricular nucleus in cardiovascular responses to glutamate receptor agonist - (:unkn) unknown (ELSEVIER SCIENCE BV, 2000)
The nuclei of the hypothalamus have been shown to be involved in central cardiovascular homeostasis. Recent studies suggest that glutamate-containing neurons have an important role in the regulation of central cardiovascular function. We report first on the effects of intracerebrally injected NMDA and non-NMDA receptor ligands on blood pressure and heart rate in conscious Sprague-Dawley rats. In the second part, we describe the effect of blockade of NMDA or kainate receptors in the paraventricular nucleus on glutamate receptor agonist-induced blood pressure responses. Intracerebroventricular injections of L-glutamic acid, NMDA and kainic acid produced increases in mean arterial pressure, Kainic acid produced significant decreases in heart rate. Microinjection of DL-2-amino-5-phosphonopentanoic acid (APV; 25 and 50 nmol), a competitive NMDA receptor antagonist, into the paraventricular nucleus blunted the increases in the mean arterial pressure evoked by intracerebroventricular injections of NMDA (1 nmol), whereas microinjection of dinitroquinoxaline (DNQX; 20, 40 and 80 pmol), which acts as an antagonist at kainate receptors, failed to antagonize the cardiovascular effects of intracerebroventricular kainic acid (10 pmol). Microinjections of NMDA (100 pmol) into the paraventricular nucleus produced presser responses, but kainic acid (5 and 10 pmol) failed to affect either mean arterial pressure or heart rate. These results suggest participation of the glutamergic system in cardiovascular regulation via NMDA receptors located within the paraventricular nucleus of the hypothalamus in rats. (C) 2000 Elsevier Science B.V. All rights reserved.
Keywords: paraventricular nucleus; excitatory amino acid; cardiovascular regulation; central; microinjection; (rat); ACID RECEPTORS; SPINAL-CORD; AMINO-ACIDS; HYPOTHALAMUS; ANTAGONISTS; RAT; EXCITOTOXICITY; STIMULATION; INCREASES; AMYGDALA